THE DEVELOPMENT OF SHADOW REGIONS AT THE PROVINCE OF CONSTANTINE CASE OF THE MUNICIPALITY OF AIN SMARA - Benmebarek Farah; Boulehouache Allaoua (International Journal of Innovative Technologies in Social Science, 2024)
In light of a massive and continuous wave of displacement for over a decade, as a result of terrorism and abandonment by the authorities of their developmental role, the countryside regions of Algeria have been found in a state of seeking for returnees who may be persuaded by the measures announced by the government in gradual manner. Besides, such a term “shadow regions” has emerged in December 2019 when the Algerian president M. Abdelmadjid Tebboune requested the preparation of a video report on the countryside regions of Algeria; however, upon presentation of such report on a giant screen to government officials after having conducted an inventory of these regions, the result was imaginably shocking, whereat 15,000 shaded regions have shown to be existing with a total population rate of more than 08 million people. Most importantly, it was much surprising that such regions are rural areas, villages and municipalities, inclusive of the surrounds the major cities such Algiers, as 299 shaded regions have been registered in the vicinity of Algiers. Subsequent to which, the Algerian government prepared an emergency program to provide basic necessities for the residents of such regions and reduce spatial differences between the territories, mainly between the countryside and the city in the same region, the same as for the Province of Constantine.